Gender: An Historical Perspective - Paola Giuliano (Institute of Labor Economics (IZA), 2017)
Social attitudes toward women vary significantly across societies. This chapter reviews recent empirical research on various historical determinants of contemporary differences in gender roles and gender gaps across societies, and how these differences are transmitted from parents to children and therefore persist until today. We review work on the historical origin of differences in female labor-force participation, fertility, education, marriage arrangements, competitive attitudes, domestic violence, and other forms of difference in gender norms. Most of the research illustrates that differences in cultural norms regarding gender roles emerge in response to specific historical situations, but tend to persist even after the historical conditions have changed. We also discuss the conditions under which gender norms either tend to be stable or change more quickly.
Keywords: N0; Z1; J16; 330; gender; cultural transmission; historical persistence